O‐glycosylation of the non‐canonical T‐cadherin from rabbit skeletal muscle by single mannose residues. Issue 22 (7th October 2013) - Winterhalter, Patrick R.; Lommel, Mark; Ruppert, Thomas; Strahl, Sabine
Abstract : O ‐mannosylation is a vital protein modification. In humans, defective O ‐mannosylation of α‐dystroglycan results in severe congenital muscular dystrophies. However, other proteins bearing this modification in vivo are still largely unknown. Here, we describe a highly reliable method combining glycosidase treatment with LC–MS analyses to identify mammalian O ‐mannosylated proteins from tissue sources. Our workflow identified T‐cadherin (H‐cadherin, CDH13) as a novel O ‐mannosylated protein. In contrast to known O ‐mannosylated proteins, single mannose residues (Man‐α‐Ser/Thr) are attached to this cell adhesion molecule. Conserved O ‐glycosylation sites in T‐, E‐ and N‐cadherins from different species, point to a general role of O ‐mannosyl glycans for cadherin function. Abstract : New workflow to detect O ‐mannosyl glycans from native tissue sources. Use of specific enzymes to discriminate sugar isomers with mass spectrometry. Identification of T‐cadherin (CDH13) as novel mammalian O ‐mannosylated protein. T‐cadherin is the first protein characterized with single O ‐linked mannose residues. O ‐mannosylation of diverse cadherin family members is suggested.